1968
DOI: 10.1152/ajplegacy.1968.215.6.1468
|View full text |Cite
|
Sign up to set email alerts
|

Development of sugar and amino acid transport by intestine and yolk sac of the guinea pig

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

1970
1970
1980
1980

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…This feature is consistent with the findings of Deren et al (1966) and Butt & Wilson (1968) in the rabbit yolk sac. They showed that the yolk sac actively transports L-valine and other neutral amino acids, while it lacks the sugar transport mechanism present in the small intestine of a maturing foetus of the same age.…”
Section: Discussionsupporting
confidence: 94%
“…This feature is consistent with the findings of Deren et al (1966) and Butt & Wilson (1968) in the rabbit yolk sac. They showed that the yolk sac actively transports L-valine and other neutral amino acids, while it lacks the sugar transport mechanism present in the small intestine of a maturing foetus of the same age.…”
Section: Discussionsupporting
confidence: 94%
“…Gly*-Leu influxes were also greater in sucklings than in adults. 4.2 and 1.6 times greater in the jejunum and ileum. respectively.…”
Section: In Adultsmentioning
confidence: 85%
“…4. Comparison of uptake rates for Gly-Gly among intestinal preparations to suckling, weanling, and adult guinea pigs.…”
Section: Adult Suckllng Jejunum Ileummentioning
confidence: 99%
“…The highest rate of active intestinal transport of both amino acids and sugars (9,10,16,22,26) occurs immediately after birth and decreases as a function of age. On the basis of kinetic studies (26), the increase in intracellular accumulation of amino acids in the 2-day-old rat intestine can best be explained by the presence of more transport sites rather than by a more efficient binding by the carrier.…”
Section: Discussionmentioning
confidence: 99%